PENYELESAIAN NUSYUZ MENURUT AL-QUR'AN DAN PENCEGAHANNYA DENGAN METODE SADD AL-ZARI'AH: 1). Analisis Penyelesaian Nusyuz Menurut Al-Qur'an. 2). Analisis Metode Sadd Al-Zari'ah dalam Mencegah Terjadinya Nusyuz. - Aria Roby Putra (SAMAWA, 2025)
This study aims to determine how to resolve nusyūz according to the Qur'an and its prevention using the sadd al-żarī'ah method. The type of research used is library research. The results of this study indicate that nusyūz can occur in both wives and husbands. The process of resolving nusyūz if done by a husband is contained in Q.S. An-Nisā' [4]: 128, namely the wife is advised to talk to her husband, be close to her husband, hold discussions and make peace with him. However, if nusyūz is done by the wife, then there are several steps that must be taken by the husband as stated in Q.S. An-Nisā' [4]: 34. First, the husband gives advice. Second, the husband separates his sleep from his wife. Third, beats the wife in a gentle and painless way. Fourth, uses a mediator from each family. The way to prevent nusyūz from happening is to love each other, respect and honor each other, maintain communication between husband and wife, understand each other between husband and wife, control the family economy, take care of biological needs, and carry out each of their rights and obligations.